2016
DOI: 10.1002/elsc.201600069
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐penetrating peptide–labelled smart polymers for enhanced gene delivery

Abstract: Highly efficient gene delivery vehicles are pursued to progress gene therapy. In this study, we developed the cell‐penetrating peptide‐labelled and degradable gene carriers for efficient external gene transfection. The cationic carriers were prepared by coupling low‐molecular‐weight polyethylenimine (PEI800) with 4ʹ4‐dithiodibutyric acid (DA), and HIV‐1 Trans‐Activator of Transcription (TAT) was conjugated to the carriers as a penetrating peptide. The resulted PEI‐DA‐TAT was able to condense plasmid DNA (pDNA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Meanwhile, CPP-triggered endocytosis is driven by CPP binding to membrane components, leading to energy- and temperature-dependent membrane invagination and uptake. For example, a study by Zhang et al utilized HIV-1 TAT conjugated to PEI800 with 4’4-dithiodibutyric acid (DA) to develop CPP-labelled degradable gene carriers for efficient gene transfection (PEI-DA-TAT) [27]. These studies showed that the cationic HIV-1 TAT peptide interacted with the negatively charged cell membrane and thereby stimulated endocytosis of the peptide along with the gene carrier system.…”
Section: Cell Penetrating Peptidesmentioning
confidence: 99%
“…Meanwhile, CPP-triggered endocytosis is driven by CPP binding to membrane components, leading to energy- and temperature-dependent membrane invagination and uptake. For example, a study by Zhang et al utilized HIV-1 TAT conjugated to PEI800 with 4’4-dithiodibutyric acid (DA) to develop CPP-labelled degradable gene carriers for efficient gene transfection (PEI-DA-TAT) [27]. These studies showed that the cationic HIV-1 TAT peptide interacted with the negatively charged cell membrane and thereby stimulated endocytosis of the peptide along with the gene carrier system.…”
Section: Cell Penetrating Peptidesmentioning
confidence: 99%
“…[161][162][163][164] In recent works, peptides like TAT, GALA and KALA were used to induce endosomal escape by enhancing the proton buffering sponge effect. 52,[165][166][167] Interestingly, histidine-rich peptides attached to poly(amidoamine) (PAMAM) dendrimers showed a significant effect on enhanced ability of endosomal escape through the balloon puncturing effect (proton sponge effect + endosomal destabilization). 168 4.1.4 Efficiency of nuclear internalization.…”
Section: Efficiencymentioning
confidence: 99%
“…7,8 Some successful attempts have been made to reduce its toxicity with simultaneous increase in the transfection efficiency, still, systemic clearance remains as an unaddressed issue. To mimic the molecular weight and structural features of bPEI (25 kDa), low molecular weight bPEI has been engineered in several ways, viz., by crosslinking (covalent or stimuli responsive), 9 attaching targeting ligands, 10 tethering dendrimers, 11 introducing hydrophobic ligands, 12 conjugating cell penetrating peptides, 13 grafting polysaccharides, 14 polyethylene glycols, 15 etc. Structurally, bPEI, being a hydrophilic polymer, lacks hydrophobic domains which have now been demonstrated to play an important role during the course of interactions with the cell membrane.…”
Section: Introductionmentioning
confidence: 99%